Performance an Experimental Study of Dual Fluids (Air-Water) Flat Plate Solar Heater (Journal of University of Babylon for Engineering Sciences, 2019)
In this study, a flat plate solar (air- water) heaters are analyzed experimentally. The collector consists of  two pipes with (12m) long, diameter (0.01905m) and a (5.54m) long air duct with a (0.01)m2 cross-sectional area. The air duct consists of four channels which the water pipes fixed parallel to the air duct in a serpentine configuration on the absorber plate. This work was performed under the weather conditions of Hilla city-Iraq with (long.44.25o E, lat.32.3o N) where the study is conducted during eight months (from July 2018 to March 2019) with different tilt angles. The performance and the effect of the mass flow rate on the collector is studied. Air, water and absorber temperatures, pressure drop and air speed are measured. Thermocouples type (K) are used to measure the temperature as this type covers the range of the studied system. A temperature data logger devices are used to display the values of the temperature. The pressure drop and air speed are measured by a U tube manometer and a digital anemometer respectively. The results show that as the mass flow rate for air and water increases the temperature for air ,water and absorber temperatures will decrease, while the efficiency of collector increase.